Why is piquant/spicy food so popular? - Spence, C (Elsevier, 2018)
The desire for piquant/spicy food has grown phenomenally over the last 500 years or so. In this review, I summarize the literature on this most intriguing of oral sensations, and summarize various explanations for why it may have become so liked by so many peoples around the world in recent years. A number of alternative hypotheses for the rise in popularity of this plant/fruit have been put forward and are briefly discussed. These include the masochistic/thrill-seeking hypothesis, the antimicrobial hypothesis, the thermoregulation/salivation-induction hypotheses, and medicinal/health/diet-based accounts.